A Case Study Based on a Complementary and Alternative Medicine Approach on an Oligoasthenoteratozoospermic Patient and its Effect on Assisted Reproductive Technology Outcome - Rupali Patil; Ritesh Jadhao; Namrata Anjankar; Akash More; Gauri Gajabe; Jarul Shrivastava (Journal of Pharmacy and Bioallied Sciences, 2024)
A couple visited the IVF clinic to seek treatment for primary infertility. A 45-year-old quadragenarian female and her 49-year-old male partner were recommended infertility treatment after 2 years of unsuccessful attempts to conceive. The woman had a recent history of dengue and chickenpox. The male partner was advised to do a semen analysis. The report showed asthenoteratozoospermia and the semen sample viscous. On the other hand, the female was diagnosed with hypothyroidism. The male patient was given a 3-month medication treatment that included probiotic supplements and cranberry juice to treat bacterial infections and urinary tract infections. The male partner also advised medication, and regular semen analysis was performed after every 3 months. The treatment plan included intrauterine insemination (IUI), which increased the possibility of pregnancy. Fourteen days following the IUI and pregnancy test, the outcomes were positive. The case illustrates the difficulties in treating primary infertility by combining reproductive procedures, medication, and lifestyle modifications. Regularly monitoring semen quality and hormonal levels is crucial in assessing treatment success. The positive outcome of IUI suggests the effectiveness of the fertility treatment plan.